Comparative Performance Evaluation Of Himachal Pradesh CoOperative Bank And Kangra Central Co-Operative Bank - Kuldeep Kumar, Navdeep Barwal, (International Journal of Scientific Research and Management (IJSRM), 2015)
Co-operative structure is a very important part of our financial system especially in rural financing. On grass root level a lot of cooperative societies’ function, which help in solving the financial needs of the rural population. District co-operative banks help these societies to raise money by way of loans. Ultimately state co-operative banks are there to finance the needs of the District co-operative banks. This three tier system is working reasonably well in India. This is parallel channel available to rural population to help them in solving their financial issues. Co-operative institutions have their own merits and demerits. Recently we have observed the fall of so many co-operative banks due to their poor financial health. This paper is an attempt to study the performance of two major co-operative banks which are operating in Himachal Pradesh viz.Himachal Pradesh State Co-operative Bank Ltd. and Kangra Central Co-operative bank Ltd. This paper aims to compare the performance of these two banks on certain parameters which would be very helpful to judge the existence and potential of these banks in future.